Waarde-uitklaring: Trojaanse perd in Suid- Afrikaanse skole? - Klerk, Jeanette de (Koers, 2000)
Value clarification: A Trojan horse in South African schools?This article entails an analysis of and a critical reflection on the value clarification approach to value-education. Questions that need to be answered are inter alia: Is value clarification perhaps an approach that offers an answer to the problem of moral pluralism in South Africa? What are the potential dangers of this approach? The origins of this approach are traced back to humanism, humanistic education and the human potential movement. It is suggested that the value clarification approach can lead to moral subjectivism, problem- and process-centredness and an overemphasis of personal emotions. Potential dangers of this approach for South Africa, where a lack of common values exists, are also highlighted. These dangers include individualism, relativism, narcissism, an egocentric “me first” attitude and the overall unacceptability of value neutrality in an educational situation, as well as of the absence of virtues and character and lack of recognition of social and historical concience. From a Biblical-educational point of view the approach of value clarification is unacceptable because of its humanistic basis. This article contains a warning for parents and teachers not to accept the value clarification approach to moral education as an easy solution to the moral threat in South African schools, but rather to see it as a potentially dangerous approach that could in fact contribute to the moral decline and erosion of authentic values.